Ethics in sport - Morgan, William J. 1948- (Champaign, IL Human Kinetics, 2018)
Ethical and moral dilemmas in sport have not diminished since Ethics in Sport was last published. The need to understand and confront such issues is at a premium, and this latest edition of Ethics in Sport will ground readers in the issues and the stakes involved. Ethics in Sport has long been known as a go-to source that tackles the moral and ethical issues in today's sport culture. This third edition retains many of the previous editions' thoughtful and timeless pieces, which speak directly to current issues, while adding 17 new essays to the mix. The inclusion of these new essays reflects the increasing sophistication of the philosophy of sport literature as well as the growth in the field. Together, these essays from well-known authors give students classic and contemporary views of topics where sports and ethics collide. This sweeping anthology of relevant and cutting-edge essays covers a variety of topics, including doping, the use of technology, gender controversies, and much more. The book is organized into five parts, with part I looking at the nature of sport, including its internal values and moral foundations. Part II investigates competition and fair play, including aspects of sportsmanship, winning, cheating, and gamesmanship. Part III examines doping and genetic enhancement in sport, including gene doping, "mechanical doping," and drug-enhanced performance. In part IV the essays explore gender and sexual equality in sport, including sex segregation and the concept of gender equality. Part V delves into issues of race, spectatorship, and politics, investigating political philosophy as it applies to sports, the fascination with sports heroes, and the ethics of supporting teams. Ethics in Sport, Third Edition, comes with an instructor guide that includes a sample syllabus, sample assignment topics, and answers to the discussion questions to facilitate class conversations. It also offers suggested class assignments for each of the five parts in the book to spur deeper discussion and understanding of the ethical issues presented in the book. With its wealth of new essays, Ethics in Sport keeps you abreast of current ethical issues in sport. As such, this text is ideal for courses in sport ethics and ethics in sport and philosophy. It is also useful as a reference for scholars, researchers, ethicists, sociologists, and philosophers of sport.
Part I. The Nature of Sport -- Chapter 1. The Elements of Sport / Bernard Suits -- Chapter 2. Thoughts on the Nature of Sport (and the Philosophy of Sport) / Graham McFee -- Chapter 3. Internalism and Internal Values in Sport / Robert L. Simon -- Chapter 4. Broad Internalism and the Moral Foundations of Sport / J.S. Russell -- Chapter 5. The Normativity of Sport: A Historicist Take on Broad Internalism / William J. Morgan -- Part II. Competition and Fair Play: Considerations of Winning, Cheating, and Gamesmanship -- Chapter 6. Sportsmanship as a Moral Category / James W. Keating -- Chapter 7. Sportsmanship / Randolph M. Feezell -- Chapter 8. On Winning and Athletic Superiority / Nicholas Dixon -- Chapter 9. Cheating and Fair Play in Sport / Oliver Leaman -- Chapter 10. In Defense of Maradona's Hand of God / Steffen Borge -- Chapter 11. Gamesmanship / Leslie A. Howe -- Chapter 12. Moral Victories / Paul Gaffney -- Chapter 13. Play and the Moral Limits of Sport / J.S. Russell -- Chapter 14. What Counts as Part of a Game? A Look at Skills / Cesar R. Torres -- Chapter 15. Intentional Rule Violations--One More Time / Warren P. Fraleigh -- Chapter 16. The Ethics of Strategic Fouling: A Reply to Fraleigh / Robert L. Simon -- Part III. The Limits of Being Human: Doping and Genetic Enhancement in Sport -- Chapter 17. Cops and Robbers? The Roots of Anti-Doping Policies in Olympic Sports / Ian Ritchie -- Chapter 18. Ethics of Technology in Sport / Sigmund Loland -- Chapter 19. Good Competition and Drug-Enhanced Performance / Robert L. Simon -- Chapter 20. Paternalism, Drugs, and the Nature of Sports / W.M. Brown -- Chapter 21. Ethics of Performance Enhancement in Sport: Drugs and Gene Doping / Bennett Foddy and Julian Savulescu -- Chapter 22. Doping, "Mechanical Doping," and Local Essentialism in the Individuation of Sports / Jon Pike -- Chapter 23. The Case for Perfection / W. Miller Brown -- Part IV. Gender and Sexual Equality in Sport -- Chapter 24. Sex Equality in Sports / Jane English -- Chapter 25. Mixed Competition and Mixed Messages / Pam R. Sailors -- Chapter 26. The Genetic Design of a New Amazon / Claudio Tamburrini and Torbjor̈n Tan̈nsjo ̈-- Chapter 27. What Is Gender Equality in Sports? / Simona Giordano and John Harris -- Part V. Select Issues in the Social Ethics of Sport: Race, Spectatorship, and Politics -- Chapter 28. Sports, Political Philosophy, and the African American / Gerald Early -- Chapter 29. Is Our Admiration of Sports Heroes Fascistoid? / Torbjor̈n Tan̈nsjo ̈-- Chapter 30. What's Wrong With Admiring Athletes and Other People? / Ingmar Persson -- Chapter 31. The Ethics of Supporting Sports Teams / Nicholas Dixon -- Chapter 32. Not Crickets? Ethics, Rhetoric and Sporting Boycotts / Edmund Dain and Gideon Calder
Includes bibliographical references
Keywords: Moral and ethical aspects -- United States; Social aspects -- United States